DESIGN OF REFRIGERATED SEA WATER PLANT FOR PRESERVATION OF FISH. - PILLAI, S AYYAPPAN (Fishery Technology, 2017)
To study the feasibility of employin<s refrigerated sea water on board fishing vessels for the preservation of fish, a pilot model has been designed, the details of which are presented in this paper,